Do Government Funding Affect Productivity of SMEs? - MBAH, Paulinus Chigozie, UGWU-OJU, Monica Obiageri, EKECHUKWU, Chijioke EDE, Titus Eguji, ODOZIOBODO Severus Ifeanyi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Development of Small and Medium Scale Enterprises (SMEs) is gaining prominence in the twenty first century. Given the scientific evidences of its meaningful contribution towards the progress of an economy hence provision of financial supports is mostly pointed as a major determinant of attaining the desired progress. In this study, Propensity Score Matching (PSM) method was used to compare the performance (productivity) between two groups of firms: those which receive government financing and those that do not. Findings revealed that the receipt of government financial support boosted productivity in both medium and small firms. This study therefore recommends that funding schemes should be made available based on the prior needs and in addition policy implementation should be more stable and translate the goals and objectives of a policy into an action